A Development of Online Lessons on the Topic of Educational Media Production for Undergraduate Students in Educational Technology and Communication Program, Sukhothai Thammathirat Open University - topothai, varangkana (ECT Education and Communication Technology Journal, 2025)
The purposes of this research were to 1) develop an online lesson on Educational Media Production for undergraduate students in the Educational Technology and Communication Program at Sukhothai Thammathirat Open University to meet the established efficiency standard; 2) compare students' learning achievement before and after using the online lesson; and 3) study students' opinions about the online lesson. The research sample comprised 39 undergraduate students in the Educational Technology and Communication Program at Sukhothai Thammathirat Open University, obtained by simple random sampling. The research instruments included 1) an online lesson on Educational Media Production; 2) two parallel forms of achievement tests for pre-testing and post-testing; and 3) a questionnaire on students' opinions toward the online lesson. Statistics for data analysis were the E1/E2 efficiency index, mean, standard deviation, and t-test. Research findings showed that: 1) the developed online lesson on Educational Media Production had an efficiency of 80.83/78.33, thus meeting the set efficiency criterion of 80/80; 2) the students who learned from the online lesson had significantly higher post-test scores than pre-test scores at the .05 level of significance; and 3) the students rated the appropriateness of the online lesson at the highest level.